THE ROLE OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN THE SCHOOL EDUCATION SYSTEM (Multidisciplinary Journal of Science and Technology, 2026)
Artificial intelligence (AI) technologies are rapidly transforming different sectors of society, including education. In recent years, AI has become an important tool in improving the quality of school education, supporting teachers, and enhancing students’ learning experiences. This article examines the role of AI technologies in school education, their advantages, challenges, and future prospects. The study also highlights the importance of integrating AI into educational systems in order to meet the demands of the digital era.